Modelling the economic performance of Recirculating Aquaculture Systems (RAS) at the farm level - Campos-González, Jorge; Gadanakis, Yiorgos; Mancini, Mattia; Bateman, Ian (My University, 2023)
Agricultural production practices are one of the most significant drivers of biodiversity loss and make farming a major contributor to greenhouse gas (GHG) emissions and water pollution. Currently, agricultural policies and farm management interventions at a farm level are designed to contribute to a transformational reform of agricultural systems to improve environmental and economic sustainability. The new Agriculture Act for the UK commits to net zero carbon emissions and policies to enhance environmental stewardship and sustainability and support the production of public goods. Introducing recirculating aquaculture systems (RAS) with farm-based renewable energy (Anaerobic Digestors, AD) provides a novel diversified enterprise for farming systems with considerable but poorly understood economic and environmental benefits. This study conducts farm-based Net Margin analysis to show that an AD unit generating up to 500 kW combined with six to 12 RAS 157 m3 units for high-value shrimp ("king prawn") production is economically viable on medium and large arable farms in the East of England at 2022 prices. Besides, we explore further key issues such as impacts on other farm activities, land use due to AD feedstock choices, use of digestate and nutrients cycling, among others.
Keywords: farm profitability; diversification; sustainability; land use; net margin